Index Kepuasan Pelanggan Anggota KSPPS Muamalah Berkah Sejahtera Perspektif Maqashid Al-Syari’ah - Mustofa Mustofa; Afiyatul Mahfudloh Faiz (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study aims to answer the question of how big is the customer satisfaction index on service quality at KPPS Muamalah Berkah Sejahtera in the perspective of Maqashid al-Syariah. The method used in this research is descriptive quantitative, the sample used is 60 people using simple random sampling technique, data collection using questionnaires and literature, while the analytical test used is the Customer Satisfaction Index (CSI) test. The results of this study indicate that the level of customer satisfaction of KKSP Muamalah Berkah members shows a satisfaction level of 87.28%, this value is in the very satisfied category. The satisfaction level of the members of the Muamalah Berkah Sejahtera KSPPS when viewed from each principle of maqasid al-Syariah gets very satisfied with the value of the CSI calculation results at a percentage level in the range of 80-100%. Of the five principles of maqasid al-Sharia, the highest value is hifdzu al-Din with a CSI value of 90.29%. Based on the results of this study, it is recommended that KSPPS Muamalah Berkah Sejahtera maintain the attributes that have been used so far and always evaluate and innovate in serving customers so that customers always feel comfortable and satisfied with their services.